The Role of Nationality-Centric Transformational Leadership in the Relationship between Business Capabilities to Sustainable Competitive Advantage and Global Marketing Performance for Franchised-SMEs Entering Global Markets - Yudianto, Agus; Santoso, Bedjo; Jusoh, Wan Noor Hazlina Wan; ., Hendar (Journal of Ecohumanism, 2025)
This report addresses Indonesian franchised-SMEs’ biggest hurdles in entering global markets, including weak managerial skills and worldwide network connectivity. Only 17 of the 400 foreign franchise stores targeted by the government have been opened, demonstrating a large disparity between potential and achievement. Innovation, management capacity, and brand distinction have been poorly studied without a coherent theoretical framework. This study highlights the understudied relevance of national values as strategic resources in global competitiveness. The research proposes Nationality-Centric-Transformational Leadership (NCTL), which combines Transformational Leadership-Theory with Resource-Based-View in competition, to fill this gap. This idea emphasises Indonesian national values as unique resources for lasting competitive advantage. The quantitative study examines internationalised Indonesian 550 franchised-SMEs’ tactics using questionnaires. The non-significant direct effects of Innovation, Learning, and Collaboration Capabilities on Global-Marketing Performance emphasise the importance of cultural adaptability and market-specific techniques. NCTL drives Global Marketing Performance and Sustainable Competitive Advantage by integrating organisational vision with cultural identity. This study positions national values as distinctive, non-substitutable resources, contributing to the Resource-Advantage-Theory-of-Competition (RATC) and Transformational Leadership-Theory. NCTL’s culturally grounded leadership approach fills the theoretical gap in religious nations’ implementation areas, boosting global competitiveness while preserving cultural authenticity.